Evaluation of productive and reproductive performance of crossbred dairy cattle reared under conventional tie barn and loose housing system during summer season - G. Josline Naviya; Manju Sasidharan; C. Balusami; Surej Joseph Bunglavan; Amritha Aravind; M.K. Aslam Muhammad (Journal of Veterinary and Animal Sciences, 2025)
The productive and reproductive performance of crossbred dairy cows kept at conventional tie barn and loose housing system were evaluated. The study was conducted in ULF FRDS, Mannuthy. Twenty crossbred dairy cows in early lactation were selected and randomly divided into two groups. Group one consists of animals housed under loose housing system (T1) and group two consists of animals housed under conventional barn system (T2). Daily milk yield and meteorological data of ambient temperature and relative humidity of both housing systems were recorded. Reproductive parameters like onset of oestrus, intensity and duration of oestrus, service period and number of services per conception were recorded.The mean ambient temperature (ºC), relative humidity () and Temperature Humidity Index of loose house and tie-barns were 29.890.15 and 30.430.98, 66.953.27 and 78.073.31, 80.680.71 and 83.300.66 respectively and were significantly different between the two housing systems.The mean values of milk yield (kg) were 14.7101.105 and 14.7801.105 in T1 and T2 at the beginning of the study and were statistically similar. During the third month there was significant reduction in milk yield(kg) of T2 while the milk yield of T1 remained consistent. The milk yield (Kg) dropped significantly for both T1 and T2 during fourth month of lactation and was 12.1600.801 and 9.9800.801 respectively. The mean service period(days) was 121.2035.808 for T1 and 157.0072.414 for T2 and median values of duration of oestrus(h) were 24.00(78) and 12.00(36) and both differed significantly.Both of them differed significantly between the treatment groups. Onset of oestrus, intensity of oestrus and number of services per conception were similar for cows housed in both housing systems. The mean daily milk yield and reproductive parameters like service period and duration of oestrous of crossbred cattle were better in loose housing system. This study shows that loose housing system could be recommended for housing dairy cattle during summer.